Morphological and molecular characterization of Xyo pseudohystrix Travassos & Kloss, 1958 (Nematoda: Oxyuridomorpha: Hystrignathidae) from Odontotaenius disjunctus (Illiger, 1800) (Coleoptera: Passalidae) from USA and discussion on its taxonomic status - Morffe, Jans; García, Nayla; Davis, Andrew K.; Hasegawa, Koichi; Carreno, Ramon A. (Zootaxa, 2019)
The females of Xyo pseudohystrix Travassos & Kloss, 1958 (Nematoda: Oxyuridomorpha: Hystrignathidae) are redescribed and illustrated with the aid of SEM. New features of the cephalic end, arrangement of the cervical spines and genital tract were observed. The taxonomic status of the species is discussed on the basis of discrepancies with the generic diagnosis of Xyo Cobb, 1898. Due to the lack of proper information on the genus the status of incertae sedis is proposed. The identity of the males was confirmed by molecular studies and the morphology of the specimens previously assigned by Christie (1932) as males of Hystrignathus rigidus Leidy, 1858 correspond to the current species. New locality records are given for the states of Georgia and Ohio, USA. The phylogenetic position of the species is inferred on the basis of the D2-D3 segment of the LSU rDNA and SSU rDNA.